2017
DOI: 10.1038/nrurol.2017.124
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant bladder cancer and prostate cancer: challenges and controversies

Abstract: Radical cystoprostatectomy (RCP) followed by bilateral pelvic lymphadenectomy and urinary diversion remains the gold-standard therapy for men with localized muscle-invasive bladder cancer (MIBC). Prostate cancer might be incidentally detected at the time of RCP with a reported prevalence of 24-51%. Typically, these patients are considered to have clinically insignificant disease, but data from emerging series challenge this assumption and suggest that some of these tumours might be aggressive, or somehow incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 65 publications
0
21
0
2
Order By: Relevance
“…Hence, to some degree, we can say that cisplatin resistance shortens the survival of advanced bladder cancer patients. To address this drawback, cisplatin-based combined therapies are increasingly used in clinical bladder cancer treatment, such as cisplatin chemotherapy combined with a PD-L1 inhibitor 24. Although some cases have shown improved clinical outcomes, drug resistance is still considered the major obstacle, and we only partially attribute this alleviation to immunity-related issues due to the PD-L1 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, to some degree, we can say that cisplatin resistance shortens the survival of advanced bladder cancer patients. To address this drawback, cisplatin-based combined therapies are increasingly used in clinical bladder cancer treatment, such as cisplatin chemotherapy combined with a PD-L1 inhibitor 24. Although some cases have shown improved clinical outcomes, drug resistance is still considered the major obstacle, and we only partially attribute this alleviation to immunity-related issues due to the PD-L1 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…We present a case of non-muscle invasive urothelial cancer metastasised to the mandible and synchronous high-risk prostate cancer (PC). Incidental finding of PC in BC patients is generally clinically insignificant; however, there is some data to suggest that synchronous high-risk PC has poor survival prognosis for non-metastatic BC and treating PC improves the progression-free survival for BC 6 7. Our case highlights the importance of considering mandibular metastasis early in the differential when a patient presents with mental nerve neuropathy as well as treating synchronous PC that may affect overall survival.…”
Section: Introductionmentioning
confidence: 79%
“…Our patient was found to have non-muscle invasive urothelial cancer that metastasised to the mandible as well as high-risk PC. PC is detected in 24%–51% of patients undergoing radical cystoprostatectomy for muscle invasive BC and up to 29% of these being high-risk PC 6. Incidentally diagnosed PC with Gleason score <6 does not affect overall survival of BC patients, but in a case series of 945 men with BC having radical cystoprostatectomy, Thomas et al found that synchronous high-risk PC with Gleason score of ≥7 and age >60 carried a poor survival prognosis for non-metastatic BC 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate cancer and bladder cancer are prevalent cancers in men. Clinical evidence has previously suggested that prostate and bladder cancers have higher concomitant incidence with a potential common pathway in tumor development (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%